Understanding Rising Concentration at the Extremes of the U.S. Income Distribution: How Important Are Income Fluctuations Among the Very Richest Households? - Thompson, Jeffrey; Bricker, Jesse; Parisi, Michael (Journal of Income Distribution®, 2021)
We explore the importance of income fluctuations at the top of the U.S. income distribution in understanding rising income concentration. Very high income families—including the top .001 percent—account for much of the recent top income growth, but are under-studied even in the literature exploring high-income groups. Using 3-year panels of tax records from 1997 to 2013 we document that top-income shares are lower—typically by about 20 percent—when measured by using a three-year income average, and that cyclical income fluctuations are greatest at the very top of the income distribution. Trends toward rising concentration over time, however, cannot be explained by these fluctuations, as growth in top-income shares is comparable for annual and three-year average income, and measured income dispersion has increased only for the very top group. Further, the probability of remaining in the highest income groups over multiple years increased over the sample period.